Personality Mental Health - Challenges and Solution: Results of the 3rd International Forum on Commitment to Mental Health - Olga B. Mikhailova; Evgeniy B. Bashkin; Nikoleta Gutvajn; Asya S. Berberyan (Peoples' Friendship University of Russia (RUDN University), 2022)
The authors present the results of the 3rd International Forum on Commitment to Mental Health, which was organized and held by the Department of Psychology and Pedagogy of the Faculty of Philology of the Peoples' Friendship University of Russia (RUDN University) in cooperation with the National Health League, ManpowerGroup and Clever Consulting LLC (Moscow, October 5-7, 2022). The work of the forum lasted three days and its program was interesting in different formats of interaction: (1) On October 5, 2022, the following events took place online: Round Table on Commitment to Mental Health Issues: Social, Psychological and Medical Aspects, Corporate Section on Best Practices: Managing Psychological Well-Being at the Organizational Level and Section on Practical Guidelines: How to Maintain and Strengthen Psychological Health (online broadcast was organized on the website: https://mentalhealthforum.ru/); (2) On October 6, 2022, RUDN University hosted the International Scientific and Practical Conference in a hybrid format at which 194 presentations were offered including: a plenary session, seven panel session, poster session and the Mental Health Film Festival; (3) On October 7, 2022, the International Charitable Sports and Psychological Festival was held (which included a concert, art therapy master classes and outdoor sports activities). The International Forum brought together more than 1000 participants, including psychologists, teachers, medical workers, teachers, graduate students and students from 25 regions of Russia and 14 countries.